2017
DOI: 10.1039/c7ra05610a
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of an amino acid permease gene family in Nicotiana tabacum

Abstract: The amino acid permease (AAP) protein family is an important class of amino acid transporter. However, little information about this gene family is available in tobacco. Here, a total number of 15, 7, and 6 fulllength putative AAP genes have been identified in the genomes of Nicotiana tabacum and progenitors of modern tobacco, Nicotiana sylvestris and Nicotiana tomentosiformis, respectively. We performed a multiple analyses of the AAP gene family in tobacco and reported data including phylogenetic relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…These functionalities could differently respond to N inputs as well as could be differently affected by factors, including photosynthetic activity and energy metabolism, with a final outcome that is very challenging to discern the regulatory network. However, an increasing interest is directed to the AAAP family, and, in our opinion, recent genome-wide analyses, such as those conducted in maize [ 94 ], potato ( Solanum tuberosum L.) [ 95 ], tobacco ( Nicotiana spp) [ 96 ], and wheat ( Triticum aestivum L.) [ 97 ] are paving the way to unravel this issue in the coming years. On the contrary, proteomics was very rarely applied in the field of amino acid nutrition in plants.…”
Section: Transporters and Transceptors Involved In Nitrogen Uptake By Rootsmentioning
confidence: 99%
“…These functionalities could differently respond to N inputs as well as could be differently affected by factors, including photosynthetic activity and energy metabolism, with a final outcome that is very challenging to discern the regulatory network. However, an increasing interest is directed to the AAAP family, and, in our opinion, recent genome-wide analyses, such as those conducted in maize [ 94 ], potato ( Solanum tuberosum L.) [ 95 ], tobacco ( Nicotiana spp) [ 96 ], and wheat ( Triticum aestivum L.) [ 97 ] are paving the way to unravel this issue in the coming years. On the contrary, proteomics was very rarely applied in the field of amino acid nutrition in plants.…”
Section: Transporters and Transceptors Involved In Nitrogen Uptake By Rootsmentioning
confidence: 99%
“…Previous research recommended that motifs 1–4 function as a transmembrane region containing transmembrane transporter activity. The existence of the same type of conserved motif recommends that members of the same family may perform similar activities [ 39 ]. In this study, we found a total of 13 unique motifs and all ZmLHTs have at least 1–4 motifs except ZmLHTs11, 13, 14, and 15.…”
Section: Discussionmentioning
confidence: 99%
“…After investigation, we found that the GmAAP members exhibit large variation in the number of exons, ranging from two to eight, while the majority of them (53%) carried seven exons. This pattern is likely conserved within plant species because nearly half of AAP genes (6 of 15) in Nicotiana tabacum contain seven exons, and over half of AAPs (18 AAPs of 34 AAPs) from Brassica napus contain six exons; 5 members of the 8 Arabidopsis AAP genes contained six exons [50][51][52].…”
Section: Gene Structure and Conserved Domain Of Gmaap Gene Familymentioning
confidence: 99%